2019
DOI: 10.1177/1178221819866181
|View full text |Cite
|
Sign up to set email alerts
|

Predicting Dropout from Inpatient Substance Use Disorder Treatment: A Prospective Validation Study of the OQ-Analyst

Abstract: Background and Aims: There is an urgent need for tools allowing therapists to identify patients at risk of dropout. The OQ-Analyst, an increasingly popular computer-based system, is used to track patient progress and predict dropout. However, we have been unable to find empirical documentation regarding the ability of OQ-Analyst to predict dropout. The aim of the present study was to perform the first direct test of the ability of the OQ-Analyst to predict dropout. Design: Patients were consecutively enlisted … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 47 publications
0
10
0
Order By: Relevance
“…Indeed, one study that examined motivational factors in treatment found that individuals who experienced slow or no progression towards their treatment goals more often had a perception of low competence which in turn led to less motivation for treatment [ 76 ]. In treatment, lack of motivation often leads to drop-out [ 77 ]. However, we did not find support for a higher drop-out rate among the poly-traumatized youth in the present study.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, one study that examined motivational factors in treatment found that individuals who experienced slow or no progression towards their treatment goals more often had a perception of low competence which in turn led to less motivation for treatment [ 76 ]. In treatment, lack of motivation often leads to drop-out [ 77 ]. However, we did not find support for a higher drop-out rate among the poly-traumatized youth in the present study.…”
Section: Discussionmentioning
confidence: 99%
“…1 Other studies have shown that dropout is common in this time frame. For example, participants with SUD dropped out after 8.4 weeks in residential treatment in Norway (Brorson, Arnevik, & Rand, 2019) and participants with methamphetamine SUD dropped out after 8.5 weeks in randomized control trials of psychopharmacological interventions (Cook, Quinn, Heinzerling, & Shoptaw, 2017). Clinicians discharged participants from the residential facility either voluntarily, by clinical recommendation, or upon incarceration.…”
Section: Treatment Termination and Progressmentioning
confidence: 99%
“…Prohibitive costs and inconsistent social-environmental support of services encouraging exercise as medicine in treatment for people with SUD presents additional challenges (49)(50)(51). Low drug treatment completion rates among people with SUD raises concerns with sustaining exercise programs adjunctive to substance use treatment, with drop-out rates of 30% to 60% common (52,53) and notable disparities in treatment completion by race (54). In a large study using national data, African Americans were less than 70% as likely to complete treatment (residential and outpatient) compared with Whites (53).…”
Section: Introductionmentioning
confidence: 99%